PENERAPAN PRINSIP TANGGUNG JAWAB MUTLAK (STRICT LIABILITY) DALAM RANGKA PERLINDUNGAN KONSUMEN - Yudha Hadian Nur; Dwi Wahyuniarti Prabowo (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2011)
Indonesia’s population is about 235 million in 2010, which becomes a potential market for producers. However, these situations become a problem because of the low education and other social economic problems which cause exploitation on consumer. Although the Law no 8, year of 1999 on consumer protection was launched by the government, the law enforcement on consumer protection is still in question. One of the alternative solutions that can be raised is the regulation of the amendment of consumer protection law by adding the principles of strict liability. It should also include the design for the area of business to be enforced, including the producers who become the subject of the provision.